Character Education By Murabbi Ruhina K.H. Yahya Syabrowi: Metaphorical Perspective - Siti Hasanah; Budik Kusworo (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
e purpose of this research is to identify and analyze the utterances of K.H. Yahya Syabrowi that contain character education values from a metaphorical perspective. This study employs a qualitative research approach to gain a deeper understanding of the educational and moral values embedded in the metaphors used by K.H. Yahya Syabrowi in his speech. A qualitative approach is considered appropriate because it allows the researcher to explore meanings, interpretations, and values conveyed implicitly through language.The data collection method used in this research is an interview technique. In total, five respondents were involved in the interview process, providing insights and interpretations related to the utterances delivered by K.H. Yahya Syabrowi. The collected data were analyzed using qualitative data analysis procedures, which include data reduction, data presentation, and drawing conclusions. These steps were applied systematically to ensure the accuracy and validity of the findings.The results of this study reveal five utterances that contain character education values viewed from a metaphorical perspective. These utterances reflect moral teachings such as responsibility, humility, perseverance, and discipline. The findings indicate that metaphors function not only as linguistic expressions but also as effective tools for shaping students’ moral character and reinforcing educational values in religious and educational contexts.